Efek Multiplier Zakat Terhadap Pendapatan di Propinsi DKI Jakarta - Al Arif, M. Nur Rianto (Al-Iqtishad: Journal of Islamic Economics, 2012)
The aim of this research is to analyze the multiplier effect of zakah revenue in DKI Jakarta, a study case at Badan Amil Zakat, Infak, and Shadaqah (BAZIS) DKI Jakarta. Least square methods is used to analyze the data. The coefficient will be used to calculate the multiplier effect of zakah revenue and it will be compared with the economy without zakah revenue. The result showed 2,522 multiplier effects of zakah revenue and 3,561 multiplier effect of economic income without zakah revenue. This suggest that the management of zakah in BAZIS DKI Jakarta still can have a significant influence on the economyDOI: 10.15408/aiq.v4i1.2079